Analysis of the Service Performance of a Driving License at the Traffic Unit of West Kutai Resort Police - Gede Pasek Muliadnyana; Hardi Warsono; Ida Hayu Dwimawanti (Jurnal Administrasi Publik (Public Administration Journal), 2021)
Driving license services in West Kutai were carried out by the Driving License Administration Service Unit. Based on the final report of Kutai Barat Police in 2016, it was noted that the issuance target was not achieved and the issuance of driving licenses decreased from 45,423 issued in 2015 to 36,086 SIMs issued in 2016. The objective of this study was to analyze the service performance of driving licenses at the Traffic Police. Kutai Barat and its supporting factors, inhibiting factors and efforts to improve its performance. Service performance was seen through service performance indicators of productivity, responsiveness, responsibility and accountability. The supporting and inhibiting factors were seen through human resources, organizational culture and community views. Meanwhile, efforts to improve were seen through efforts to increase work and plan for work improvement activities. The research method used was descriptive qualitative. The results indicates that the performance of the Traffic Unit of West Kutai Police was good, the supporting factors for the performance were organizational culture and community views, while the inhibiting factor was human resources.